A Survey on the Small Data - Smitha, KA; Sangeetha, B; Ramu, BS; Ashoka, DV (International Journal of Computer Sciences and Engineering, 2025)
Small data deals with data that is small in size for human comprehension. About one quarter of the human brain is involved in visual processing and the only way to comprehend "big data" is to reduce them to small, this data can be informative, accessible and actionable. Small data typically provides information that answers a specific question or addresses a specific problem. This paper highlights the concept of small data and explains how to overcome the difficulties of big data. Small data is about placing the small datasets where it is actually needed. By considering the data of any size solves a specific problem, instead of the massive data which does not solve the problem.